Peningkatan Hasil Belajar Peserta Didik pada Tema Bermain di Lingkunganku melalui Pembelajaran Covid-19 Metode Blended Learning di Kelas II.C SDN 04 Payakumbuh Semester Ganjil Tahun Pelajaran 2021/2022 - Sorniati Sorniati (Journal on Education, 2022)
This study aims to obtain information on how to improve student learning outcomes on the theme of playing in my environment through COVID-19 learning using the blended learning method in class II.C SDN 04 Payakumbuh odd semester in the 2021/2022 academic year. This research is a Classroom Action Research. The research was conducted at SDN 04 Payakumbuh. The subjects in the Classroom Action Research (PTK) that the author did were Class II.C students at SDN 04 Payakumbuh, North Payakumbuh District, totaling 29 people. This Classroom Action Research (TK) was conducted in the 2021/2022 academic year semester 1 for three months, namely August, September, October 2021. The research procedure consisted of two cycles with four research stages starting from planning, implementation, observation and reflection. Data collection in Class II.Cni action research includes: observation sheets, test sheets, documentation, and online sheets. The data taken by the observer is processed using a percentage (quantitative) technique. Based on the results of the research conducted, it can be concluded that using the COVID-19 Learning Blended Learning Method can improve student learning outcomes in each cycle, this can be seen from the mastery of learning knowledge which increases from pre-cycle 76.21 = 55%, cycle I 84.83 = 69%, and cycle II 97.24 = 97%. For mastery learning skills, namely pre-cycle 77.59 = 55%, cycle I 88.62 = 72%, and cycle II 96.90 = 93%.